Antipsychotic-Associated Weight Gain and Clinical Improvement Under Clozapine Treatment. Issue 1 (January 2022) - Garriga, Marina; Mallorquí, Andrea; Bernad, Sonia; Ruiz-Cortes, Victoria; Oliveira, Cristina; Amoretti, Silvia; Mezquida, Gisela; Bioque, Miquel; Molina, Oriol; Gómez-Ramiro, Marta; Vieta, Eduard; Bernardo, Miquel; et al.
Abstract: Background: Antipsychotic-associated weight gain is a common adverse effect with several negative outcomes in the clinical evolution of patients, which might also affect patients' self-identity from physical appearance and imply treatment discontinuation. However, recent research has drawn attention to an unexpected clinical improvement associated with weight gain, mostly in patients under treatment with clozapine or olanzapine. Methods: Twenty-three treatment-resistant psychosis patients initiating clozapine were evaluated. Longitudinal psychopathological assessment through the Positive and Negative Syndrome Scale (PANSS) and anthropometric evaluation were performed at baseline, week 8, and 18. Results: Body mass index (BMI) change during clozapine treatment was associated with clinical improvement measured with PANSS total score at week 8 ( P = 0.021) while showed a trend at week 18 ( P = 0.058). The PANSS general score was also associated with weight gain at week 8 ( P = 0.022), whereas negative subscale score showed a trend at week 8 ( P = 0.088) and was associated between week 8 and 18 ( P = 0.018). Sex differences applied at week 8 for PANSS total score, where clinical improvement was significantly associated with BMI in male subjects ( P = 0.024). We also stratified for time to initiate clozapine, finding significant associations in negative symptom at week 8 ( P = 0.023) and week 18 ( P = 0.003) for subjects, which started clozapine after 3 years of illness. Conclusions: Our results suggest that in subjects initiating clozapine, clinical improvement is associated with BMI increase, mostly in negative symptom and in patients after 3 years of antipsychotic use. Our findings were already described in the preantipsychotic era, suggesting some pathophysiological mechanism underlying both conditions.